PENGARUH PERSEPSI HARGA DAN KEPERCAYAAN KONSUMEN DI APLIKASI SHOPEE TERHADAP MINAT BELI PRODUK FASHION SAAT PANDEMI COVID-19 PADA MASYARAKAT MILENIAL DI KOTA MEDAN - Hana Fila Delfia Surbakti; Anne Rumondang Malau (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2021)
This study aims to determine the effect of price perception and consumer trust on buying interest in fashion products on the Shopee application during the covid 19 pandemic. The number of samples in this study was 100 respondents. From the results of the multiple regression analysis test, the price perception variable has a positive effect on buying interest of 0.104 and the variable of consumer confidence has a positive effect on buying interest of 0.255. From the results of the t-test, the price perception variable has a positive and insignificant effect on buying interest, it can be seen that there is the lowest answer to the fourth statement, namely